Regional Characterization and Resource Evaluation of Paleocene and Eocene Coal-bearing Rocks in Pakistan - Durrani, N.A.; Warwick, P.D. (Journal of Himalayan Earth Sciences, 1991)
Field work drilling, and other related studies carried out from 1985 to 1988 to assess the quantity and quality of the coal resources of southern Sindh. Sixty-eight holes drilled in the Lakhra/Jherruck, Thatta, and Indus East coal fields indicate that presently known and mined coal fields in southern Sindh are not isolated coal occurrences. Rather, much of southern Sindh, including the Thar Desert, is underlain by strata that contain coal beds. More than 400 core and mine samples were collected for proximate and ultimate analysis and determination of major, minor and trace elements; also, lithologic logs were prepared from description of rock cuttings and core. Original coal resources of 1,080 million tones have been estimated for 7 out of 9 coal zones in parts of the area, where coal-bed thicknesses range from a few centimeters to 5 m. In the Sonda/Jherruk area, 3, 700 million tons of coal have been identified, the thickest coal bed intercepted being 6.3 meters. The apparent rank of the coal in these fields ranges from lignite A to sub-bituminous C. Averaged analytical results on an as received basis indicate the coal beds contain 28.4 % moisture, 18.3 % ash, 4.7 % sulfur, 25.2 % fixed carbon, 27.9 % volatile matter, and 33.1 % oxygen. Average calorific value for Lakhra coal samples is about 3, 660 Kcal/kg, whereas that of Sonda/Jherruk samples is about 3,870 Kcal/kg. Geophysical logs were obtained for the drill holes, and cores and rock cuttings are available from the GSP for further study and reference. The second phase of the project began in 1987 with surface exploration in the Salt Range coal field of Punjab Province, the Sor Range and Khost-Sharig-Harnai coal fields of Baluchistan, and the Makarwal and Cherat coal fields of NWFP. These are briefly discussed here.